Institutional and economic determinants of Corporate Social Responsibility disclosure by banks: institutional perspectives - Silva, Maria José; Azevedo, G.; Oliveira, J. (4th Symposium on Ethics and Social Responsibility Research, 2017)
This article analyzes the determinants of Corporate Social Responsibility disclosure by banks. Drawn on the New Institutional Sociology, it combines Campbell’s (2007) institutional theory with Dillard’s et al. (2004) model of organizational dynamic change. Specifically, the present article assesses if economic and institutional conditions explain CSR disclosure strategies of thirty listed and unlisted banks from six countries in the context of the recent 2007/2008 Global Financial Crisis. The annual reports and social responsibility reports of the largest banks in Canada, UK, France, Italy, Spain and Portugal were content analyzed. Findings suggest that economic factors did not influence CSR disclosure. Institutional factors associated with the legal environment, industry self-regulation, and the organization’s commitments in maintaining a dialogue with relevant stakeholders are crucial elements in explaining CSR reporting. Consistent with the Dillard’s et al. (2004) model, CSR disclosure by banks not only stem from institutional legitimacy processes, but also from strategic ones.